Diabetic Retinopathy: Two Faces of the Same Coin. (2008) - Muñoz, Silvia; Sanz, Silvia; Planas, Núria
Abstract : We report two contrasting cases of diabetic retinopathy to illustrate vascular and retinal abnormalities in this condition. In the first case, mild diabetic retinopathy is diagnosed in an asymptomatic patient with diabetes mellitus of recent onset. The second patient has severe diabetic retinopathy, causing vision loss as a consequence of poor metabolic control.